THEORETICAL STUDY ON ROUGHNESS FACTORS OF INVOLUTE SPUR GEAR TRANSMISSION - GAO ChuangKuan; ZHOU ZhongKe (Jixie qiangdu)
The surface roughness data of test-pieces with transverse profiles were firstly measured by a roughness profile measuring analyzer. With the help of the Fourier nonlinear approximation the measured data were used to form a roughness function which was superimposed to film thickness equation and a mixed thermal elastohydrodynamic lubrication model was then established. Based on the model,280 sets of numerical calculations were carried for both medium and heavy duty transmissions through changing the roughness values. The results show that the contact stress τmax,rfor rough teeth surfaces is increased by 5%compared with the contact stress τmax,sfor smooth teeth surfaces when the root mean square roughness of tooth surface σ≤0. 3μm; While the τmax,ris increased by 15- 20% compared with the τmax,swhen σ ≥ 0. 5 μm. At the end,several theoretical formulas for determining the roughness factors are created based on the multiple regression analysis of the above calculated results.